Clarke, Bruce. (Ed.) (2020). Posthuman Biopolitics: The Science Fiction of Joan Slonczewski. Palgrave - Alex, Soorya (Journal of Posthumanism, 2024)
Posthuman Biopolitics (2021) is a thoroughly researched collection of critical studies, which focuses solely on the science fiction novels of microbiologist Joan Slonczewski within the framework of posthumanism. These critical studies amply and substantially throw light upon the posthuman world of biological/ecological upheavals. They take the readers on a futuristic journey into the narrative diversities of liminal worlds where humans coexist with other organisms, actors, and objects on an egalitarian plane of existence. Bruce Clarke’s book anthologizes the novel age of the Anthropocene and provides fictional insights that texture Slonczewski’s work, through a diverse range of essays contributed to by a galaxy of academics, including; Christy Tidwell, Chris Pak, Derek J. Thiess, Sherryl Vint, Colin Milburn, and Alexa T. Dodd.